Subsolidus structure of the MgO – Al₂O₃ – FeO – TiO₂ system - Borysenko, Oksana; Logvinkov, Sergey; Shabanova, Galina; Pitak, Yaroslav; Ivashura, Andrii; Ostapenko, Igor (Lviv Polytechnic National University, 2022)
The subsolidus structure of the fourcomponent system MgO – Al₂O₃ – FeO – TiO₂ was studied in six temperature ranges. Geometric-topological characteristics of the phases of the system under study have been determined, topological graphs of the relationship of elementary tetrahedrons have been constructed, their volumes, degrees of asymmetry for all temperature ranges have been found. The optimal regions of compositions for the production of spinel-containing materials have been predicted, which are within the limits of elementary tetrahedra: MgO – FeO – Mg₂TiO₄ – MgAl₂O₄, FeAl₂O₄ – Mg₂TiO₄ – FeO – Fe₂TiO4, FeAl₂O₄ – Mg₂TiO₄ – MgAl₂O₄ – FeO and FeAl₂O₄ – MgTiO₃ – MgAl₂O₄ – Al₂O₃ .

Досліджено субсолідусну будову чотирикомпонентної системи MgO – Al₂O3 – FeO – TiO₂ в шести температурних інтервалах. Визначено геометро-топологічні характеристики фаз досліджуваної системи, побудовано топологічні графи взаємозв'язку елементарних тетраедрів, визначено їхні об’єми, ступінь асиметрії для всіх температурних інтервалів. Прогнозовано оптимальні області складів для виробництва матеріалів, що містять шпінель, які лежать у межах елементарних тетраедрів: MgO – FeO – Mg₂TiO₄ – MgAl₂O₄, FeAl₂O₄ – Mg₂TiO₄ – FeO – Fe₂TiO₄, FeAl₂O₄ – Mg₂TiO₄ – MgAl₂O₄ – FeO and FeAl₂O₄ – MgTiO₃ – MgAl₂O₄ – Al₂O₃.
Субсолідусна будова системи MgO – Al₂O₃ – FeO – TiO₂
Keywords: subsolidus structure; tetrahedration; geometric-topological characteristics; magnesium-alumina spinel; hercynite; quandilite; субсолідусна будова; тетраедрація; геометро-топологічні характеристики; алюмомагнезіальна шпінель; герциніт; квандиліт